Profile and management of hypertensive urgencies and emergencies in the emergency cardiology department of a tertiary hospital: a 12-month registry. (27th October 2021) - Fragoulis, Christos; Dimitriadis, Kyriakos; Siafi, Eirini; Iliakis, Panagiotis; Kasiakogias, Alexandros; Kalos, Theodoros; Leontsinis, Ioannis; Andrikou, Ioannis; Konstantinidis, Dimitrios; Nihoyannopoulos, Petros; Tsivgoulis, Georgios; Thomopoulos, Costas; et al.
Abstract: Aims: Currently there are scarce epidemiological data regarding prevalence, clinical phenotype, and therapy of hypertensive urgencies (HU) and emergencies (HE). The aim of this article was to record the prevalence, clinical characteristics, and management of patients with HU and HE assessed in an emergency department (ED) of a tertiary hospital. Methods and results: The population consisted of patients presenting with HE and HU in the ED (acute increase in systolic blood pressure (BP) ≥ 180 mmHg and/or diastolic BP ≥120 mmHg with and without acute target organ damage, respectively). Of the 38 589 patients assessed in the ED during a 12-month period, 353 (0.91%) had HU and HE. There were 256 (72.5%) cases presented as HU and 97 (27.5%) as HE. Primary causes for both HU and HE were stress/anxiety (44.9%), increased salt intake (33.9%), and non-adherence to medication (16.2%). Patients with HU reported mainly dizziness/headache (46.8%) and chest pain (27.4%), whereas those with HE presented dyspnoea (67%), chest pain (30.2%), dizziness/headache (10.3%), and neurological disorders (8.2%). In HE, the underlying associated conditions were pulmonary oedema (58%), acute coronary syndrome (22.6%), and neurological disorders/stroke (7.2%). All HE cases were hospitalized and received intensive healthcare, including dialysis. Conclusion: This 1-year single-centre registry demonstrates a reasonable prevalence of HU and HE contributing to the high volume of visits to the ED. Stress, increased salt intake and non-adherence were main triggers of HE and HU. Dizziness and headache were the prevalent symptoms of HU patients while heart failure was the most common underlying disease in patients with HE. Graphical abstract: